PENGGUNAAN CELANA KETAT TERHADAP KELUHAN FLUOR ALBUS PADA MAHASISWI UNIVERSITAS WIDYA DHARMA KLATEN - Ambarsari, Dwi Wanito (JURNAL SABHANGA, 2022)
Introduction of reproductive health problems are often encountered in the life cycle of women and one of these health problems is fluor albus. The purpose of this study was to determine the relationship between the use of tight pants and the complaints of fluor albus in Widya Dharma University students, Klaten. Method used is observational analytic with a case control approach. The samples in this study were students of the Faculty of Psychology and Health, Widya Dharma University, Klaten, with a case group and a control group using purposive sampling technique. The independent variable is fluorine albus, while the dependent variable is the use of tights. Analysis of the data in this study using Kendall's tau-b analysis. The process in this research is characterized by discussing the findings and drawing conclusions from the results obtained. Results show that the value of sig. (2-tailed) is 0.030 < 0.005. Conclusion that there is a significant relationship between the use of tights and complaints of flour albus